SEASONAL DISTRIBUTION TOTAL SUSPENDED SOLID IN RANGSANG BARAT COASTAL WATERS MERANTI ISLAND REGENCY RIAU PROVINCE - Nadida, Putri; Mubarak, Mubarak; Efriyeldi, Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtracTSS (Total Suspended Solid) is suspended materials has a negative impact on water quality because it reduces the penetration of sunlight into the water body, the turbidity of the water increases which causes growth disruption for the producer organism. This research was conducted in April 2018 in the West Rangsang waters of Meranti island regency. Aimed to determine the distribution of the concentration of TSS during the West and East season by using Landsat 8 Acquisition image analysis in March 2018 and Landsat 8 Acquisition june 2017. The research method is a survey and determination of sampling points by means of purposive sampling. TSS in situ analysis was carried out in the sea chemistry laboratory by gravimetric method, and analysis of image data using ER Mapper 7.0 and Notepad++ applications. Analiysis of insitu TSS data at each station was obtained with a range of 65.4 – 115.8 mg/l, from the results of image processing in the western season obtained TSS values of 0 – 109 mg/l and the results of image processing in the East season obtained TSS values of 0 – 120 mg/l. In general, the TSS distribution patterns generated by the image in the West seasen spread of TSS which leads close to the coast tends to be higher than the TSS distribution in the East season and vice versa the more towards the sea the TSS concentration is lower.The result of TSS data in situ with the result of image analysis in the West and East seasons of the stations in the West season in higher than in the East season.The result of current velocity measurement is 0.22 – 0.55 m/s, visibility 6.5 – 38 cm, turbidity 43.23 – 225 NTU, salinity 25.01 – 28 ppt and depth of 3.5 – 5.11 m. Keyword: TSS, Rangsang Barat, ER Mapper, Notepad++,Landsat.